AN ACCESSORY FISSURE AND LOBE OF THE LEFT LUNG: CASE REPORT - Mustafa, Dr. Amal Yousif Ahmed Elhaj; Elamin, Dr. Asma Mohammed (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Anatomical variations of the lung lobes and fissures are very common. They have beendescribed by many authors, using imaging techniques, fewer studies were done using grossanatomy. The left lung classically has one fissure, the oblique fissure and two lobes namelythe upper and lower lobes. In the present case, we report a variant oblique fissure of leftlung. Such abnormal fissures are clinically important for identifying broncho-pulmonarysegments.